2022
DOI: 10.29303/jppipa.v8i2.1264
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Guided Discovery Learning Model with SETS Approach Assisted by E-Modul Chemistry on Scientific Literacy of Students

Abstract: Chemical concepts are not only taught abstractly by the teacher, but students also need to do it independently to better understand, of course, with the help of the teacher. So it is necessary to intervene in learning such as the right way in learning the right way. The purpose of this study was to demonstrate the effect of implementing a guided discovery learning model with the SETS approach with the help of a chemistry module on the scientific skills of SMA Negeri 1 Padang class XI students. The method of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…The analysis conducted was the effectiveness of the android-assisted discovery learning model to improve students' scientific literacy. Based on the results of a review of the articles in Table 1, it was found that the discovery learning model can improve students' scientific literacy skills (Bahtiar et al, 2022;Berliana et al, 2023;Budiarti et al, 2021;Maghfiroh et al, 2023;Priadi et al, 2022;Purnamawati &;Basuki, 2021;Rahmawati et al, 2023;Warlinda et al, 2022;Widiyana et al, 2021;Winarni et al, 2020;Yolida et al, 2022). The discovery learning model is a model that requires students to find their concepts through a series of activities they do.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis conducted was the effectiveness of the android-assisted discovery learning model to improve students' scientific literacy. Based on the results of a review of the articles in Table 1, it was found that the discovery learning model can improve students' scientific literacy skills (Bahtiar et al, 2022;Berliana et al, 2023;Budiarti et al, 2021;Maghfiroh et al, 2023;Priadi et al, 2022;Purnamawati &;Basuki, 2021;Rahmawati et al, 2023;Warlinda et al, 2022;Widiyana et al, 2021;Winarni et al, 2020;Yolida et al, 2022). The discovery learning model is a model that requires students to find their concepts through a series of activities they do.…”
Section: Discussionmentioning
confidence: 99%
“…The physics e module can improve students' scientific literacy skills by obtaining an N-Gain score of 0.4 in the medium category. Developing physics e-modules based on discovery learning is efficacious in improving students' scientific literacy skills Warlinda et al (2022). Applying the guided discovery learning model with the SETS approach supported by the chemistry e-module significantly influences the scientific literacy of SHS 1 Padang grade XI students Budiarti et al (2021).…”
mentioning
confidence: 99%
“…Therefore, the YouTube-assisted discovery learning model activates the way of thinking, making students more critical. According to Warlinda et al [34], applying a discovery learning model using the science, environment, technology, and society (SETS) approach supported by the Chemistry E module significantly affects scientific abilities. The application of the discovery method and YouTube digital media makes learning more interesting and fun.…”
Section: Differences In Cognitive Learning Outcomes and Critical Thin...mentioning
confidence: 99%
“…Home gaining knowledge of coverage packages withinside the Industrial 4.zero Revolution generation additionally require digital gaining knowledge of system consisting of digital modules. Electronic modules can help unbiased gaining knowledge of and may enhance students' clinical literacy abilties and gaining knowledge of outcomes (Kimianti & Prasetyo, 2019;Raharjo et al, 2017;Warlinda et al, 2022).…”
Section: Preliminary Researchmentioning
confidence: 99%